Boosting Output Performance of Triboelectric Nanogenerator via Mutual Coupling Effects Enabled Photon‐Carriers and Plasmon. Issue 4 (23rd November 2021) - Chen, Xin; Zhao, Yanjun; Wang, Fayang; Tong, Daqiao; Gao, Lingxiao; Li, Dongxiao; Wu, Liangke; Mu, Xiaojing; Yang, Ya
Abstract: Boosting the output performance of triboelectric nanogenerators via some unique methods is always a meaningful way to speed up their commercialization. However, the available approach to boost performance is mainly restricted to one physics effect based and the basic research of boosting performance via mutual coupling effects is little research. Herein, a new strategy is creatively proposed based on charge traps from mutual coupling effects, generated from g‐C3 N4 /MXene‐Au composites, to further promote the output performance of triboelectric nanogenerator. It is found that photon‐generated carriers coupling surface plasmon effect enables composites filled into tribo‐material with visible light is an excellent value in boosting performance. The charge traps from mutual coupling effects for boosting performance are analyzed theoretically and verified by experiments. The output power of boosting‐triboelectric nanogenerator (TENG) achieves a sixfold enhancement (20 mW) of normal TENG with polydimethylsiloxane (PDMS) in ambient conditions. This work provides a profound understanding of the working mechanism of mutual coupling effects boosting the performance of TENG and an effective way for promoting TENG output. Abstract : A novel strategy based on charge traps from mutual coupling effects enabled photon‐carriers and plasmon generated from g‐C3 N4 /MXene‐Au composites has been utilized to further promote the output performance of triboelectric nanogenerator.